Biomechanical analysis of gender differences in movement characteristics and full-body impact using accelerometers during running - Choi, J.-E.; Park, S.-K. (Korean Journal of Sport Biomechanics, 2025)
Objective: The purpose of this study was to investigate gender differences in kinematic, kinetic and impact characteristics of the whole body during running. Method: 15 females (height: 160.87 ± 5.37 cm, weight: 53.19 ± 4.15 kg, age: 28.60 ± 6.21 yrs.) and 15 males (height: 174.94 ± 5.93 cm, weight: 72.65 ± 8.23 kg, age: 24.27 ± 4.04 yrs.) participated in this study. All subjects performed a 6-minute run at 2.8 m/sec on an instrumented treadmill. Three-dimensional accelerometers were attached to the four anatomical positions such as the distal tibia, proximal tibia, 5th lumbar and head. Gait parameters, biomechanical variables (lower extremity joint and trunk segment angle, range of motion, angular velocity, ground reaction force and moment) and acceleration variables (impact acceleration, shock attenuation) were calculated during the stance phase of the running. Independent t-test and 1D-SPM were used with an alpha level of .05. Results: Female runners showed decreased step length with increased step frequency compared to male runners. The maximum angle of knee abduction and trunk right rotation increased in females compared to males, whereas trunk flexion increased in males. The hip range of motion in the sagittal plane increased in females, while the trunk range of motion in the transverse plane increased in males. The maximum angular velocity of joint and segment increased in females compared to males. Also, loading rate and braking force increased in females. Ankle plantar flexion and knee extension maximum moment increased in males, while knee adduction and hip flexion maximum moment increased in females. The vertical and resultant impact accelerations increased in all segments in females compared to males. The shock attenuation of horizontal resultant acceleration (from the distal tibia to the head) also increased in females compared to males. Conclusion: Gender differences may exist in the shock mechanisms during running as female runners experience greater accumulated joint loads at the same intensity of exercise level compared to male counterparts. Therefore, it is suggested that using gender specific sporting gears and exercise interventions may be helpful to prevent potential lower leg injuries for females.